Rizogênese in vitro e aclimatização de Luehea divaricata Mart. & Zucc. - Silva, Karol Buuron da (2016)
In front of the need to recover the original forest cover of the Atlantic Forest, it is necessary to adopt restoration programs of deforested areas using native species. Luehea divaricata Martius et Zuccarini, popularly known as açoita-cavalo, is a native tree specie of the Atlantic Forest biome widely used for the recovery of areas. It is a forest species that has its wood used for many different purposes, which contributed to the reduction of their natural populations, causing difficulties to find viable seeds of the species. Given this fact, the micropropagation becomes a viable alternative for the production of high quality seedlings, providing thus the formation of healthy populations for use in restoration projects of degraded areas. This way, this study aimed to optimize the rooting in vitro process and acclimatization of the species, and, for this, different concentrations of salts of the WPM nutritive medium for in vitro root formation shoots of Luehea divaricata were initially evaluated. Then, the effects of the addition indolebutyric acid (IBA) as a treatment "pulse" and naphthaleneacetic acid (NAA) in the nutritive medium were studied for rooting in vitro specie. The effect of the combination of vermiculite volume with the nutritive medium WPM/2 in root formation in vitro of Luehea divaricata was also analyzed in this study, as well as the implication of sucrose and different concentrations of substrates in the species acclimatization. The nutritive medium WPM/2 showed the most promising results for the development of Luehea divaricata, reaching values of 44,52% in the formation of primary roots after 45 days of in vitro culture. Treatment "pulse" with different concentrations of IBA and the use of NAA concentrations are not efficient for in vitro root formation in Luehea divaricata. The combinations of 20mL of nutritive medium + 15cm³ vermiculite, 20mL of nutritive medium + 30cm³ of vermiculite and 30mL of nutritive medium + 30cm³ of vermiculite were more promising for in vitro root formation in the species, providing averages of 39,61% in the rooting after 45 days of cultivation. Finally, for acclimatization in vitro and ex vitro substrates based on bio-stabilized pinus bark or based on turf, calcareous calcitic and composted pinus bark may be used, independently of sucrose concentrations tested during in vitro cultivation.